A pedagogical model for effective online teacher professional development—findings from the Teacher Academy initiative of the European Commission. (19th January 2022) - Hertz, Benjamin; Grainger Clemson, Hannah; Tasic Hansen, Daniella; Laurillard, Diana; Murray, Madeleine; Fernandes, Luis; Gilleran, Anne; Rojas Ruiz, Diego; Rutkauskiene, Danguole
Abstract: During their careers, teachers experience change in education policy, societal trends, and cultural shifts in pedagogical thought, requiring continual adaptation and innovation of their practices. Coupled with this is an assumed intrinsic desire to progress, whether as part of their own subject expertise, or with a view to taking on a role as leader in school management or a specialist area. Effective support and opportunities for teachers to develop and apply their competences is crucial for maintaining both motivation and high standards in the profession. However, many teachers across Europe claim to struggle to have access to effective forms of continued professional development coupled with the numerous demands already made on their work. On‐site courses with opportunities for peer learning remain popular but demand time and are not financially cost‐effective in reaching a large number of teachers, nor are they viable during pandemic restrictions. By exploring the pedagogical model of the online courses of the European Commission's Teacher Academy in the context of these challenges, this article discusses how an effective, collaborative approach to online continued professional development can be developed as a way of addressing both teacher and education system needs.